We and the public sector/ edited by S.M. Patil and Raj K. - S.M. Patil (ed.) (New Delhi, 1988)
The Public Sector in India has come a long way during the last four decades. With a mere five enterprises having an investment of Rs.29 crores in 1951, the Public Sector today in its fold has 226 enterprises having an investment of Rs 61,600 crores. Actually the size of Public Sector both in terms of number of enterprises and investment therein is enormous if other Central Government enterprises and investment therein is enormous if other Central Government enterprises and the State Governments enterprises is taken into reckoning.
Keywords: Government business enterprises-India